(untitled) (Proceedings of Southern Federal University. Philology, 2019)
Irina M. Yaroslavskaya (Rostov-on-don, Russian Federation) The aim of this article is to consider some problems of the use of method of projects in the process of learning Russian as a foreign language at preUniversity stage of education. Methodical organization of project activities of international learners in the writing of creative works at the initial stage was the object of the study. The development of creative abilities of foreign students in non-native language was the subject of research. In the process of studying there were used the following methods of research: a) analyses of domestic and foreign scientific and methodical literature on the use of ideas of project activities in educational institutions; b) own experience on teaching foreign language to Russian students and Russian Language to foreign learners; c) monitoring speech activities of foreign learners; d) monitoring the succession of realization of research work by foreign learners. Practice shows that it is actual nowadays. Taking part in preparation of project foreign learners get to know the stages of research work, which will be necessary for their future studying in the University, improve language skills, learn to defend their point of view, to work in a team. Project activities help the learners obtain the skills in independent work. Key words: method of projects, foreign learners, pre-University training stage, research work, creative works. DOI 10.23683/1995-0640-2019-1-226-234